2005
DOI: 10.1111/j.1365-2249.2005.02872.x
|View full text |Cite
|
Sign up to set email alerts
|

Detection ofin vitrointerferon-γ and serum tumour necrosis factor-α in multidrug-resistant tuberculosis patients

Abstract: SummaryMultidrug-resistant tuberculosis (MDR-TB) is known as having a poor prognosis with a weak response to therapy and very high death rates. The aim of this work was to assess the immune response to the RD1-encoded antigen ESAT-6 of Mycobacterium tuberculosis in MDR-TB patients and compare to non-resistant (NR) TB patients and healthy controls (HC). Evaluation of interferon (IFN)-g g g g production showed that, although 55% of the MDR patients were responsive to ESAT-6, they produced lower IFN-g g g g level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0
3

Year Published

2006
2006
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 37 publications
2
15
0
3
Order By: Relevance
“…Decreased IFN-γ production has previously been described in patients infected with multidrug-resistant strains. (12,13) Our study produced similar results, which corroborates reports that drug-resistant strains downregulate the Th1 response, and that the degree of downregulation is strain-dependent. In summary, we observed heterogeneous cytokine immune responses for a panel of clinical M. tuberculosis strains.…”
Section: Brief Communicationsupporting
confidence: 81%
“…Decreased IFN-γ production has previously been described in patients infected with multidrug-resistant strains. (12,13) Our study produced similar results, which corroborates reports that drug-resistant strains downregulate the Th1 response, and that the degree of downregulation is strain-dependent. In summary, we observed heterogeneous cytokine immune responses for a panel of clinical M. tuberculosis strains.…”
Section: Brief Communicationsupporting
confidence: 81%
“…This result may be related to the lack of host selective pressure suffered by the laboratory strain H37Rv. Low in vitro Th1 responses to different M. tuberculosis antigens have been observed in MDR-TB patients, such as impaired IFN-␥ production (4,16,25,26,33) and increased IL-4 production by CD4 ϩ T cells stimulated by a lipid extract of H37Rv (50). Likewise, in our study, both MDR-TB and S-TB patients showed an impaired expression of IFN-␥ in CD4 ϩ and CD8 ϩ T cells, irrespective of the tested strain; therefore, this might be ascribed to the altered Th1/Th2 profile characteristic of advanced disease (13).…”
Section: Discussionmentioning
confidence: 99%
“…Protective immunity against TB is mediated by a Th1-type immune response characterized by high levels of interleukin-12 (IL-12) from infected macrophages and gamma interferon (IFN-␥) from antigen-specific T cells, which control and contain infection in the lungs (24). Peripheral blood mononuclear cells (PBMC) from MDR-TB patients have been shown to poorly respond in vitro to H37Ra whole bacilli, purified protein derivative (PPD), and specific antigens, such as ESAT-6 and the 30-kDa protein (16,25,26,33). Furthermore, increased IL-4 secretion by CD4 ϩ T cells after H37Rv total lipid stimulation was observed in MDR-TB patients (50).…”
mentioning
confidence: 99%
“…IL-18, another cytokine linked to Th1 pathway, may also have a putative role in cellmediated protection against mycobacterial infection [235]. Tumour necrosis factor (TNF)-a, released largely from macrophages, contributes to protecting the host by promoting granuloma formation [236]. However, TNF-a can also cause tissue necrosis under subversive T-cell influence.…”
Section: Adjunctive Surgery For Pulmonary Tuberculosismentioning
confidence: 99%